Effects of market and climatic conditions over a gas turbine combined cycle integrated with a Heat Pump for inlet cooling. (15th May 2021) - Giugno, Andrea; Sorce, Alessandro; Cuneo, Alessandra; Barberis, Stefano
Highlights: Inlet cooling of combined cycle gas turbine by heat-pump enhances performance. The cooling potential is reduced by the electrical market conditions. Real data used to evaluate the impact of six electricity markets and climatic zones. Optimization of revenues for different heat-pump size considering off-design. Economic analysis of the integrated system against market and climate conditions. Abstract: The growing need of dispatchable units, capable to balance the variable renewable energy electrical production leads to the development of strategies aimed at increasing power plants operational flexibility and global efficiency in part-load operation. A highly efficient heat pump (integrated in a conventional natural gas combined cycle is here proposed as a flexibility enhancement solution. Such concept, applied to power oriented combined cycle, allows to modify the compressor intake temperature with a consequent increase of the power production. While this operation for open cycle gas turbine is beneficial also to electric efficiency, combined cycles' efficiency is less sensitive to the temperature variation and thus more influenced by the auxiliary consumption. The selection of the proper heat pump size for the proposed layout was based on an optimization process considering both combined cycle and heat pump off-design performance. After a statistical analysis of climatic data and their correlations with energy market condition for the six Italian price zones, the models developed were applied to assess the thermoeconomic potential of the proposed layout. This work highlights how a proper optimization process influences both revenues and size optimization and to highlight how such integrated system can be selected at its best considering typical market and climatic frames. The ratio between the air-cooled heat pump electrical consumption and the electrical combined cycle capacity that maximize power production increase was found to be 1/100. This finding can be extended to the others world Humid subtropical climate and Mediterranean hot summer climates zones. It is underlined how electrical market conditions could jeopardize the installation profits even under favourable climatic potential reducing the optimal economic heat pump size. Using off-design curves and optimization algorithm in performing coupling analysis appears to be more effective, with respect to simplified calculations under unfavourable economic and climate conditions.